Device for germicidal air disinfection by ultraviolet radiation - Семенов, Анатолій Олексійович; Кожушко, Григорій Мефодійович (Eastern-European Journal of Enterprise Technologies, 2014)
Air often becomes a source and a distributor of pathogens, that’s why one of the ways of germicidal public safety is the introduction of UV air disinfection methods. The UV methods, unlike chemical methods do not change the air composition and its organoleptic properties. The studies of these methods are especially noteworthy for scientists. The results of theoretical and experimental studies have shown that the methods, used in the design of closed-type devices for germicidal air disinfection, take into account the volume dose of bacterial inactivation, which depends on the chamber geometry. This disadvantage is solved by using the surface dose that does not depend on the chamber geometry and is a function of bacterial species. The design of the UV closed-type device for germicidal air disinfection is proposed. This device is made in the form of a cylindrical chamber from a special material, in which a germicidal lamp is placed symmetrically. The device capacity is calculated from the minimum irradiance conditions, which provides the required surface dose on any section of the inner surface of the chamber.